isiXhosa Translation of the Patient Health Questionnaire (PHQ-9): A Pilot Study of Psychometric Properties [Stage 1] - Mudra Rakshasa-Loots, Arish; Laughton, Barbara (Frontiers in Psychiatry, 2022)
Depression is a debilitating illness, and stigma associated with it often prevents people from seeking support. Easy-to-administer and culturally-specific diagnostic tools can allow for early screening for depression in primary care clinics, especially in resource-limited settings. In this pilot study, we produced the first open-access isiXhosa-language version of the nine-item Patient Health Questionnaire (PHQ-9), a well-validated measure of depression incidence and severity, using a transcultural translation framework. We validated this isiXhosa PHQ-9 in a small sample (N = XX) of adolescents living with HIV in Cape Town, South Africa who speak isiXhosa at home. Participants had previously completed the ASEBA Youth Self Report (YSR) form, and responses from the YSR were used as a gold standard to validate the isiXhosa PHQ-9. We found that this translation exhibited a [high/satisfactory/low] internal consistency, Cronbach's alpha = XX. Inter-item and item-total score correlations were r = XX and XX, respectively. The PHQ-9 demonstrated a [high/satisfactory/low] degree of correlation with the YSR, r = XX for PHQ-9 total scores and T scores in the "Withdrawn/Depressed" component of the YSR and r = XX for the "Affective Problems" component. The isiXhosa PHQ-9 showed diagnostic sensitivity and specificity of XX and XX, respectively. Area under the Receiver Operating Characteristic (ROC) curve was AUC = XX, indicating [high/satisfactory/low] diagnostic accuracy. Our findings suggest that this isiXhosa-language version of the PHQ-9 exhibits [high/acceptable/low] reliability, validity, and diagnostic accuracy in this sample of isiXhosa-speaking adolescents living with HIV. Further large-scale studies are needed to verify the findings of this pilot study. If validated, this isiXhosa PHQ-9 may be an invaluable culturally-specific tool for clinicians serving Xhosa people in identifying clinical or sub-clinical depression.